Implementasi UU No. 16 Tahun 2019 Tentang Dispensasi Nikah Di Tinjau Dari Hukum Islam - Muhammad Akil; Maryati Maryati (Universitas Muslim Indonesia, 2022)
A marriage dispensation is an exception or permission given to the applicant to marry in the Religious Court. This study employs a sampling technique due to the nature of the data, namely data on marriage dispensation requests at the Makassar Religious Court Class 1A in 2019 and 2020. The results of this study indicate that in accordance with Law Number 16 of 2019, article 7 paragraph (1), which is a revision of Law Number 1 of 1974, prospective brides who are not yet 19 years old must obtain a marriage dispensation. The most important condition for obtaining a marriage dispensation is a refusal from the Office of Religious Affairs (KUA) of the original model letter N9, which states that the bride and groom have not yet reached the age of 19. The average application before promulgation was 6.6667, while the average application after being enacted was 4.9167. However, because sig (2-tailed) > i.e., 0.226 > 0.05, the final conclusion of the research accepted by H0 is that there is no effect because there is no significant difference in the application for marriage dispensation between before and after Law Number 16 of 2019. Therefore, the implementation of Law No. 16 of 2019 at the Makassar Religious Court class 1A cannot be known in detail based on the results of a comparison of data before and after its stipulation, the results of which show no significant differences.